Developing endurance - Reuter, Ben (Illinois : Human Kinetcs, 2012)
Runners, cyclist, swimmers, rowers, triathletes, and ultradistance athletes must sustain performance at a high level to come out on top. Developing endurance shows how to achieve optimal stamina to race your best through science-based aerobic, anaerobic, and resistance training.
Physiology of endurance sport training -- Endurance tests and assessments -- Endurance training principles and considerations -- Endurance sport nutrition and hydration -- Aerobic endurance development -- Anaerobic and muscle endurance development -- Resistance training for endurance sports -- Running -- Cycling -- Swimming -- Triathlon
Includes bibliographical references and index.
Keywords: DEVELOPING ENDURANCE